Guest‐induced Assembly of Bis(thiosemicarbazonato) Zinc(II) Coordination Nanotubes. (23rd March 2017) - Paterson, Brett M.; White, Keith F.; White, Jonathan M.; Abrahams, Brendan F.; Donnelly, Paul S.
Abstract: A Zn II complex of the dianionic tetradentate ligand formed by deprotonation of glyoxal‐bis(4‐phenyl‐3‐thiosemicarbazone) (H2 gtsp) is a [3+3] trinuclear triangular prism. Recrystallization of this complex in the presence of either CO2, CS2, or CH3 CN leads to the formation of [4+4] open‐ended charge‐neutral tetranuclear coordination nanotubes, approximately 2 nm in length and with internal dimensions large enough to accommodate linear guest molecules, which serve to template their formation. Upon removal of the templating molecules the nanotubes demonstrated reversible sorption of CO2 with an isosteric enthalpy of sorption of 28 kJ mol −1 at low loading.